Elemental diet directly affects chemotherapy-induced dermatitis and raw wound areas - Harada, Koji (Mol Clin Oncol, 2020)
Elental(®) is an L-glutamine-rich elemental diet (ED) that has been widely used in Japan as a nutritional supplement for malnourished patients. In addition, Elental(®) has been successfully used in the management of chemotherapy-induced mucositis in cancer patients. Recently, it was also reported that Elental(®) can effectively reduce chemotherapy-induced oral mucositis in patients with oral squamous cell carcinoma, and can also reduce mucositis and dermatitis in animal models. However, it is unclear whether oral intake or topical application of Elental(®) can act directly on chemotherapy-induced oral mucositis or dermatitis. The aim of the present study was to investigate the possible direct healing effect of Elental(®) on chemotherapy-induced dermatitis and raw wound areas in a mouse model. Dermatitis and raw wounds were induced in nude mice by administration of 5-fluorouracil (5-FU) (via gastric tube) and mechanical injury (using a metal brush or a surgical knife). We then compared the outcome following oral or topical application of Elental(®) in these mice. The effect of Elental(®) on the growth and migration ability of the human oral keratinocyte cell line, HOK, was also examined using MTT and migration assays, respectively. In the mouse model, both oral administration and topical application of Elental(®) reduced 5-FU-induced dermatitis and healed raw wound areas more effectively compared with the topical application of saline. The MTT assay revealed that Elental(®) exerted a growth-promoting effect on HOKs. In addition, Elental(®) enhanced the ability of HOKs to migrate, as demonstrated by the migration assay. These findings demonstrated that the topical application as well as the oral intake of Elental(®) exerted a direct healing effect on chemotherapy-induced dermatitis or raw wound areas. The data also indicated that oral intake of an ED may exert a direct healing effect on chemotherapy-induced oral mucositis.